Evaluation of the knowledge and compliance with pharmacological treatment in hypertensive and type 2 diabetic patients in a family health unit - Rodriguez, Patricia Vera; Mastroianni, Patricia [UNESP]; Silva, Lourdes Raquel Samaniego; Lugo, Gladys Beatriz; Maciel, Olga Yolanda; Maidana, Gladys Mabel (Fundacion Pharmaceutical Care Espana, 2023)
Introduction: The level of patients' knowledge about their medications is highly related to the improvement of their rational use and the results of the pharmacotherapy. The aim of this study was to assess the knowledge and the compliance with the pharmacological treatment in hypertensive and type 2 diabetic patients in a family health unit of the city of Luque.Method: It was carried out an observational, descriptive and cross-sectional study. The selection was done by convenience and the information was obtained through interviews which took place during the home visits from May to June, 2021. A structured questionnaire was used and included social demographic data and questions of the Dader method and the Morisky-Green test modified.Results: Among the 50 interviewed patients, 80% were women, with an average age of 63,04 & PLUSMN; 11.39 years with a low level of education. 100% were hypertensive and 38% were diabetic too. The most prescribed antihypertensive, both, alone or combined, were Ioasar tan Potassium (50%) and Enalapril Maleate (18%). 42% of the diabetic patients used oral antidiabetics and 58% insulin. 100% of the patients ignored their treatment and the compliance did not exceed 22% for both diseases.Conclusions: The patients do not know their treatment and the compliance is very low. Thus, it is necessary the intervention of a pharmacist and the implementation of educational strategies that can help to improve the level of knowledge and the adherence to treatment.
Keywords: hypertension; type 2 Diabetes Mellitus; treatment; knowledge; compliance; evaluation